Adaptasi pada Pasien Gagal Ginjal Kronik yang Melakukan Terapi Hemodialisis Berdasarkan Teori Sister Calista Roy: Literatur Review - dedi krismiadi; Hasniah Dina; Apriyanti; Nazaruddin; Mery Eka Yaya Fujianti (Indonesian Health Science Journal, 2024)
One of the nursing theories that can be applied in implementing adaptation for chronic kidney failure patients is Roy's adaptation theory. If the patient can adapt to his condition, he will be able to create a quality life so that he can maintain health. Objectives: The aim of this paper is to identify ROY adaptation in hemodialysis patients. Method: The process used to carry out scoping is that the reviewer searches for several research journal articles published through electronic databases. The electronic databases used include: ProQuest. The keywords used are for journals in English, namely Roy adaptation model theory and nursing care and chronic kidney failure. Search results found in ProQuest as many as 3,739 journals. Google Scoolar, as many as 1,800journals and Science Direct as many as 180 journals found were specified based on inclusion criteria, namely 1) articles published in full text and in English, 2) articles published in the 2013-2023 period. After adjusting based on inclusion criteria, the remaining articles is 1,984. There were 7 main journals included in this literature review. Results: Roy's adaptation model which presents physiological relationships, self-concept and role function. Conclusion: Roy's adaptation can provide an adaptive response for hemodialysis patients in carrying out daily life with quality life.